Managing Cover Crops for Improved Soil Health - Ramdeo Seepaul; Sheeja George; Joel Love; D. W. Wright; C. Mackowiak; A. Blount (EDIS)
This publication aims to help growers and researchers understand the role of cover crops in improving soil health. The document provides recommendations on managing cover crops and describes the benefits of growing cover crops. Written by R. Seepaul, S. George, J. Love, D. W. Wright, C. Mackowiak, and A. Blount, and published by the UF/IFAS Agronomy Department, revised January 2023.